Heterogeneous Ru(iii) oxidation catalysts via 'click' bidentate ligands on a periodic mesoporous organosilica support. Issue 22 (31st August 2016) - Clerick, Sander; De Canck, Els; Hendrickx, Kevin; Van Speybroeck, Veronique; Van Der Voort, Pascal
Abstract : A 100% monoallyl ring-type Periodic Mesoporous Organosilica (PMO) is prepared as a novel, versatile and exceptionally stable catalytic support with a high internal surface area and 5.0 nm pores. Abstract : A 100% monoallyl ring-type Periodic Mesoporous Organosilica (PMO) is prepared as a novel, versatile and exceptionally stable catalytic support with a high internal surface area and 5.0 nm pores. Thiol–ene 'click' chemistry allows straightforward attachment of bifunctional thiols (–NH2, –OH, –SH) which, exploiting the thioether functionality formed, give rise to 'solid' bidentate ligands. [Ru(acac)2 (CH3 CN)2 ]PF6 is attached and complex formation on the solid is studied via density functional theory. All resulting solid catalysts show high activity and selectivity in alcohol oxidation reactions performed in green conditions (25 °C/water). The PMO catalysts do not leach Ru during reaction and are thus easily recuperated and re-used for several runs. Furthermore, oxidation of poorly water-soluble (±)-menthol illustrates the benefits of using hydrophobic PMOs as catalytic supports.